Mechanisms and predictors of ischemic mitral regurgitation at rest and on exertion in patients at early stage of myocardial infarction - K. G. Adamyan; A. L. Chilingaryan; N. G. Mkrtchyan; L. G. Tunyan (Российский кардиологический журнал)
Aim. Determination of the mechanisms and predictors of ischemic mitral regurgitation (IMR) at rest and on exertion in patients at early stage of myocardial infarction (MI).Material and methods. Seventy-seven patients with inferoposterior MI and 79 patients with anteroseptal apical MI were examined on the 7th day at rest and after exertion. We determined the degree of IMR (according to the PISA method), posteromedial and anterolateral papillary muscle (PM) displacement, closure height of the mitral valve (MV), systolic and diastolic mitral valve orifice area, volume of the left ventricle (LV), LV contractility index, deformation of the infarction regions, general LV deformation, deformation and systolic dyssinchrony of the PM.Results. IMR was more common in inferior MI (42% vs 28%). LV volumes in cases with anteroseptal apical MI and IMR were greater and LV deformation was less than in patients without IMR. In inferoposterior MI and IMR, differences were observed in the index of local contractility and function of the posteromedial PM. The differences in MI of both localizations and IMR compared with MI without IMR were the areas of the mitral orifice and dyssinchrony of the PM. The degree of IMR after exertion did not depend on the degree of IMR at rest. Predictors of IMR at rest in MI of both localizations were the apical displacement of MV closure and the area of the mitral orifice. In inferoposterior, posteromedial PM displacement, deformation of the infarcted areas, PM dyssinchrony were also predictors. In anteroseptal apical MI, the area of the mitral orifice was the predictor of IMR. Predictors of anteroseptal apical MI after physical exertion after inferior MI were mitral orifice areas, contractility index, displacement and deformation of the posteromedial PM. In anteroseptal apical MI, the IMR predictors were MV closure height and systolic area of mitral orifice.Conclusion. The study confirms the significance of changing the spatial orientation of the MV structures in MI of both localizations, impaired regional contractility in inferoposterior MI and LV volume in anteroseptal apical MI at early stage of the disease.